Vascular dysfunction by myofibroblast activation in patients with idiopathic pulmonary fibrosis and prognostic significance - E.R. Parra; R. Falzoni; V.L. Capelozzi (Brazilian Journal of Medical and Biological Research, 2012)
In this study, we demonstrated the importance of telomerase protein expression and determined the relationships among telomerase, endothelin-1 (ET-1) and myofibroblasts during early and late remodeling of parenchymal and vascular areas in usual interstitial pneumonia (UIP) using 27 surgical lung biopsies from patients with idiopathic pulmonary fibrosis (IPF). Telomerase+, myofibroblasts α-SMA+, smooth muscle cells caldesmon+, endothelium ET-1+ cellularity, and fibrosis severity were evaluated in 30 fields covering normal lung parenchyma, minimal fibrosis (fibroblastic foci), severe (mural) fibrosis, and vascular areas of UIP by the point-counting technique and a semiquantitative score. The impact of these markers was determined in pulmonary functional tests and follow-up until death from IPF. Telomerase and ET-1 expression was significantly increased in normal and vascular areas compared to areas of fibroblast foci. Telomerase and ET-1 expression was inversely correlated with minimal fibrosis in areas of fibroblast foci and directly associated with severe fibrosis in vascular areas. Telomerase activity in minimal fibrosis areas was directly associated with diffusing capacity of the lung for oxygen/alveolar volume and ET-1 expression and indirectly associated with diffusing capacity of the lungs for carbon monoxide and severe fibrosis in vascular areas. Cox proportional hazards regression revealed a low risk of death for females with minimal fibrosis displaying high telomerase and ET-1 expression in normal areas. Vascular dysfunction by telomerase/ET-1 expression was found earlier than vascular remodeling by myofibroblast activation in UIP with impact on IPF evolution, suggesting that strategies aimed at preventing the effect of these mediators may have a greater impact on patient outcome.